Pengukuran Loyalitas Mahasiswa dengan Pelayanan Pegawai Administrasi dan Kepuasan Mahasiswa - Rahmat Hidayat; Tulus Rohana (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
This study aims to determine the effect of administrative staff service and student satisfaction on student loyalty. This research was conducted at the Polytechnic X Medan from September 2019 to completion. The primary data in this study were in the form of questionnaires and direct interviews with parties related to the research carried out such as to get student perceptions about administrative staff services, student satisfaction, and student loyalty. In addition, this study also uses secondary data in the form of references from books and articles published in journals. Questionnaires that have been designed were distributed to 186 students who became respondents. The observed variables consist of employee service, satisfaction, and student loyalty. After the questionnaires were distributed to the respondents, the results were made in tabulated form and then tested for validity and reliability. The research data were analyzed by quantitative descriptive using multiple linear regression. Hypothesis testing with coefficient of determination test, simultaneous test and partial test. The results of this study indicate that simultaneously and partially administrative employee services and student satisfaction have a positive and significant effect on student loyalty.